Surface triggering receptor expressed on myeloid cells-1 (sTREM1) in critically ill children: a prospective observational controlled study - Elsaeed Rashad Fouda; Sara Hosny Abd Elghany; Thoria Ahmed Omar; Alyaa Ahdy Abdelaziz (The Turkish Journal of Pediatrics, 2025)
Background. In children admitted to the pediatric intensive care unit (PICU), early detection of risk factors and alarming indicators improves the prognosis and may even save lives. Several prognostic markers and scores have been studied in children who are seriously ill. Recently, surface triggering receptor expressed on myeloid cells-1 (sTREM1) has been studied in many infectious and non-infectious settings; however, there is little information on critically ill children. Our aim is to evaluate the sTREM1 level in critically ill children and assess its prognostic role.